2012
DOI: 10.11591/edulearn.v6i2.148
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Education in Term of Knowledge and Attitude through Mother Support Group

Abstract: Pengetahuan dan sikap sangat penting untuk keberhasilan pemberian susu badan. Tujuan penyelidikan ini adalah untuk menyelidik pengaruh pengetahuan dan sikap dalam hal pemberian susu badan pada para ibu Indonesia yang bergabung dalam program Kelompok Pendukung Ibu (KP-Ibu). Seramai 221 ibu menyertai penyelidikan ini. Regresi bertingkat digunakan untuk menilai pengaruh pengetahuan dan sikap terhadap pemberian susu badan. Hasil kajian menunjukkan bahawa pengetahuan dan sikap mempengaruhi pemberian susu badan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
0
7
1
3
Order By: Relevance
“…Our findings were consistent with previous studies by Parkinson et al (2010) and by Cinar et al (2015), who found that personal social support is essential for both breastfeeding and maternal attachment. According to Handayani et al (2012), social support, attitude, self‐efficacy and knowledge are critical during breastfeeding. Handayani et al also found that there is a strong correlation between social help and parental support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were consistent with previous studies by Parkinson et al (2010) and by Cinar et al (2015), who found that personal social support is essential for both breastfeeding and maternal attachment. According to Handayani et al (2012), social support, attitude, self‐efficacy and knowledge are critical during breastfeeding. Handayani et al also found that there is a strong correlation between social help and parental support.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with previous studies by Parkinson et al (2010) and by Cinar et al (2015), who found that personal social support is essential for both breastfeeding and maternal attachment. According to Handayani et al (2012) Various studies point out that mothers who receive emotional and physical support have a higher maternal attachment (Abuhammad et al, 2019;Lamb, 2012). The culture and practices of Jordanian people contribute to the assumed maternal capabilities and the ability to care for an infant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Handayani et al indicated that mothers who had high KAP regarding breastfeeding exclusively breastfed their babies. Knowledge has a strong effect on breastfeeding practice ( p < 0.001) and attitude has a weak influence on breastfeeding practice ( p = 0.02) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Pengetahuan adalah pemahaman teoritis maupun praktis yang diperoleh melalui pendidikan. Jenis pengetahuan terdiri dari: pengetahuan deklaratif untuk mempelajari tentang konsep dan pengetahuan prosedural untuk mempelajari prosedur atau metode penyelesaian masalah 13 Berdasarkan hasil penelitian pada tabel 3. didapatkan bahwa peserta SKB sebagian besar memiliki tingkat pengetahuan yang kurang. Kuesioner yang diisi oleh orang tua dari 10 pertanyaan terdapat 7 pertanyaan yang jawabannya salah.…”
Section: Pembahasanunclassified